1982
DOI: 10.1136/bmj.285.6355.1658-a
|View full text |Cite
|
Sign up to set email alerts
|

Factors protective against retinopathy in insulin-dependent diabetics free of retinopathy for 30 years.

Abstract: index of an increase in circulating adrenal oxysteroids.' Depression of eosinophil concentrations has been shown in response to surgery,2 trauma,3 exercise,4 and emotional stress.4 The low eosinophil counts found in acute severe asthma are compatible with a stress response related to the higher cortisol concentrations.5 The authors' argument that eosinophilia has a beneficial effect in chronic asthma while eosinopenia allows the development of acute asthma might lead one to expect that corticosteroids would pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…This result was supported by many earlier studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), but not by others (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In the younger-onset group, there was some suggestion of a relationship between smoking and the incidence of any retinopathy in both univariate and multivariate analyses, but it was weak.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…This result was supported by many earlier studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), but not by others (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In the younger-onset group, there was some suggestion of a relationship between smoking and the incidence of any retinopathy in both univariate and multivariate analyses, but it was weak.…”
Section: Discussionsupporting
confidence: 44%
“…Cigarette smoking, a characteristic with potential for modification, if proved to be a risk factor for retinopathy, would have great public health implications for the prevention of this complication. Some studies have found an association between cigarette smoking and diabetic retinopathy (3)(4)(5)(6)(7)(8)(9)(10)(11)(12), whereas others have not (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Many of these studies are hampered by their cross-sectional design or small sample sizes.…”
mentioning
confidence: 93%